Chemical synthetic biology - Luisi, P. L.; Chiarabelli, Cristiano (Hoboken : Wiley, 2011)
Chemistry plays a very important role in the emerging field of synthetic biology. In particular, chemical synthetic biology is concerned with the synthesis of chemical structures, such as proteins, that do not exist in nature. With contributions from leading international experts, Chemical Synthetic Biology shows how chemistry underpins synthetic biology. The book is an essential guide to this fascinating new field, and will find a place on the bookshelves of researchers and students working in synthetic chemistry, synthetic and molecular biology, bioengineering, systems biology, computational.
Front Matter -- Colour Plates -- Introduction / Pier Luigi Luisi -- Nucleic Acids. Searching for Nucleic Acid Alternatives / Albert Eschenmoser -- Never-Born RNAs: Versatile Modules for Chemical Synthetic Biology / Davide De Lucrezia, Fabrizio Anella, Cristiano Chiarabelli, Pier Luigi Luisi -- Synthetic Biology, Tinkering Biology, and Artificial Biology: A Perspective from Chemistry / Steven A Benner, Fei Chen, Zunyi Yang -- Peptide Nucleic Acids (PNAs) as a Tool in Chemical Biology / Peter E Nielsen -- Peptides and Proteins. High Solubility of Random-Sequence Proteins Consisting of Five Kinds of Primitive Amino Acids / Nobuhide Doi, Koichi Kakukawa, Yuko Oishi, Hiroshi Yanagawa -- Experimental Approach for Early Evolution of Protein Function / Hitoshi Toyota, Yuuki Hayashi, Asao Yamauchi, Takuyo Aita, Tetsuya Yomo -- Searching for Totally Random Amino Acid Sequences / Cristiano Chiarabelli, Cecilia Portela Pallares, Anna Quintarelli -- Complex Systems. Synthetic Genetic Codes as the Basis of Synthetic Life / J Tze-Fei Wong, Hong Xue -- Toward Safe Genetically Modified Organisms through the Chemical Diversification of Nucleic Acids / Piet Herdewijn, Philippe Marliere -- The Minimal Ribosome / Hiroshi Yamamoto, Markus Pech, Daniela Wittek, Isabella Moll, Knud H Nierhaus -- Semi-Synthetic Minimal Living Cells / Pasquale Stano, Francesca Ferri, Pier Luigi Luisi -- General Problems. Replicators: Components for Systems Chemistry / Olga Taran, Gunter von Kiedrowski -- Dealing with the Outer Reaches of Synthetic Biology Biosafety, Biosecurity, IPR, and Ethical Challenges of Chemical Synthetic Biology / Markus Schmidt, Malcolm Dando, Anna Deplazes -- The Synthetic Approach in Biology: Epistemological Notes for Synthetic Biology / Pier Luigi Luisi -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Biomolecules -- Synthesis; Science; Chemical engineering; Natural history; Chemistry; Engineering; Electronic books